Pengaruh Bahan Tambah Serat Ijuk Terhadap Sifat Mekanik Beton SCC (Self Compacting Concrete) - Rizal Rizaldi; Dendi Yogaswara (Jurnal Kendali Teknik dan Sains, 2023)
In the current development of concrete innovation technology, there are also expensive materials that are cheap as concrete additives for the efficiency of the cost of making concrete. cheap and can be used as concrete innovation. The purpose of adding palm fiber fiber is to improve the quality of concrete, both compressive strength and split tensile strength. The method used in this study was experimentation by adding palm fiber to the SCC concrete mixture with variations of 2%, 4% and 6%. As for the addition of chemical substances, the superplasticizer admixture aims to make it easier for SCC concrete to achieve a slump flow value that meets the requirements. After testing, the highest compressive strength test specimen is BC 1 2% palm fiber worth 19.38 MPa and for the lowest compressive strength test is BC 2 6% palm fiber worth 5.46 MPa. And for the split tensile strength test the highest is BC 4 2% palm fiber worth 9.47 MPa and for the lowest split tensile strength test is BC 3 6% palm fiber worth 5.82 MPa.